FEATURES OF RUSSIAN GRAPHICS AND ALPHABET, CLASSIFICATION OF SOUNDS, ORTHOEPY (Eureka Journal of Language, Culture & Social Change, 2025)
The article examines the key features of the Russian graphics and alphabet, the basic principles of classification of sounds of the Russian language and the role of orthoepy in ensuring correct pronunciation. The material reveals important aspects of the sound system and its reflection in writing, and also emphasizes the importance of observing orthoepic norms in modern speech.
Keywords: Russian graphics, alphabet, classification of sounds, vowels and consonants, phonetics, orthoepy, pronunciation norms, stress, vowel reduction, softness and hardness of consonants.